(3aj GdCfSGHs - (3GdYHjOj GdYdhqj, GdLhGfj GdeGdcj, CHh Ydj, TQa GdOjf, eMeO Hf CSYO Hf Ydj Hf eYeQ, J (B588 (3g`s
(3ChdgG (B:s
... (3hdG jRGd LfGH YRg eWhbG HbdGFO GdKfGA hGdMeO hCHbGg EeGeG (B... (3haQWG dQhGI GdNHQ hceG ddJQLjM Hjf GdUMjM hGdLQjM EP de jRd GdbOhI dCgd GdMOjK aj GdbOje hGdMOjK (B...s
(3BNQgG (B:s
... (3aJRhLgG YHO Gddg Hf GdRHjQ Hf GdYhGe hNQLJ ejehfI HfJ CejQ GdeDefjf Ydj Ydjg GdSdGe HYO CNJgG CeQgG Hj Edi YHO Gddg Hf Ybjd Hf CHj WGdH Ke Nda YdjgG JeGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\31s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdJGQjNs